The effect of culture media on the number and bioactivity of marine invertebrates associated fungi - AGUS TRIANTO; OCKY KARNA RADJASA; MADA TRIANDALA SIBERO; Agus Sabdono; DWI HARYANTI; WA ODE MARDHIYYAH ZILULLAH; ANNISA RORO SYANINDYTA; MUHAMMAD SYAIFUDIEN BAHRY; PRASTYO ABI WIDIANANTO; MUHAMAD HELMI; HARYO DWITO ARMONO; SUPRIADI; YASUHIRO IGARASHI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Trianto A, Radjasa OK, Sibero MT, Sabdono A, Haryanti D, Zilullah WOM, Syanindyta AR, Bahry MS, Widiananto PA, Helmi M, Armono HD, Supriadi, Igarashi Y. 2020. The effect of culture media on the number and bioactivity of marine invertebrates associated fungi. Biodiversitas 21: 407-412. Marine ecosystem is rich with microorganisms such as bacteria and fungi either as free-living or in association with macro-organisms. Marine invertebrates provide suitable habitats for fungi by supplying space, food, and other chemicals stuff that in some cases is a reciprocal relationship or called mutualism symbiotic. Some marine invertebrates have interesting activities that are useful for human life such as anticancer, antifungal, and antibacterial. Many reports indicated that the fungal growth and their production of bioactive compounds were highly affected by the media or nutrition. In order to understand the effect of media on the number and bioactivity of the isolates, we collected the samples of marine invertebrates from two locations in Makassar. Invertebrate specimens were collected by hand during SCUBA diving at 3-10 m depths. The fungi were isolated by tapping method either on potato dextrose agar (PDA) or poor marine agar (PMA). The samples were collected from the Samalona water as much as 16 specimens that provided 30 and 18 fungal isolates on PDA and PMA, respectively, while, from the Barrang Cadi water, a total 14 specimens were collected to provide 12 and 3 isolates on PDA and PMA, respectively. All fungi from PMA inhibited the V. harveyi, V. vulnificus, and V. parahaemolyticus with weak, medium, and strong activities, while, the isolates from PDA were mostly not active against the Vibrios. Based on the molecular analyses, the active isolates were identified as Aspergillus flavus, A. oryzae, A. aculeatus, Talaromyces minioluteus, Hypocrea jecorina, Gliomastix murorum, Myrothecium inundatum, and Curvularia avinis. In conclusion, the isolates from PMA showed higher potential as source of antivibrio substances.